Teatro científico como elemento de mobilização para o aprendizado de química e física no ensino fundamental - Rodrigues, Aleilson da Silva (2018)
This study is an analysis of the use of the Scientific Theater as a practice that can mobilize the students of the 9th Year to the learning of Chemistry and Physics, since the introductions of such sciences integrate the curriculum of the 9th Year of Elementary Education in the classes of Natural Sciences. The objective was to understand the contributions of the Scientific Theater to the attribution of meaning to the sciences Chemistry and Physics and to the process of Science Teaching in the 9th of Elementary School. One of the central theoretical foundations for this work is Bernard Charlot's Theory of Relation with Knowing (2000; 2009; 2013), dealing with mobilization; (2009a, 2009b), Krasilchick and Marandino (2007), Cachapuz et al (2011) Carvalho et al. al (2010) and Delizoicov, Angotti and Pernambuco (2009). The study was carried out in Santana do Ipanema-AL, in two schools, one in the rural area and the other in the urban area, considering the different socio-cultural contexts in a class of 9th Year of each school. The methodology adopted was based on the combination of different strategies, namely: application of questionnaires, workshop realization incorporating the Scientific Theater and Knowledge Balance. The data produced by the B.S. and recorded in field diaries were analyzed from a qualitative and quantitative perspective in order to better understand the phenomena investigated in order to respond to the objectives intended by the study. The data produced by the students and registered in the observations allowed to understand the Scientific Theater as a practice that can associate the development of skills with the learning in sciences, provide the perception of the historical and dynamic construction of Chemistry and Physics, the understanding of its fields of action and relation between the areas, assigning meaning, by the processes of distance-objectification-systematization. The theatrical activity can introduce questions and content for further deepening, the imaginary materialization of structures to deal with concepts. Also constructed were the perceptions that, in order to mobilize the student, attention must be paid to aspects such as the various positions of students on the activity and the development of the protagonism of the student, the expansion of the concept of science and theater classes, besides the recreation, attention to the dynamics of groups and relation "actor" and "spectator", to integrate others methodologies of science teaching and other areas of knowledge.